CORRECTION: The role of social support in the relationship between different coping strategies and the emotional distress in the bereaved elderly - Ljevaja, Milica; Janic, Ognjen; Lazić, Milica; Krstić Joksimović, Kristina (Psihološka istraživanja, 2023)
In our article: "The role of social support in the relationship between different coping strategies and the emotional distress in the bereaved elderly" published in No. 1, Vol. 26 in Psihološka istraživanja journal, on page 100. under the section "Sample and procedure", the information that this article is part of the project "The elderly in Vojvodina: factors of successful aging" financed by the Provincial Secretariat for Higher Education and Scientific Research (project number 142-451-2665/2021-01) was excluded by our mistake. Therefore, as authors of this article, we are providing you with a corrected version, and we apologize to all readers for such an oversight.